2020
DOI: 10.1002/jbm.a.36964
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of fresh and preserved amniotic membrane for guided bone regeneration in mice

Abstract: Thanks to its biological properties, the human amniotic membrane (HAM) can be used as a barrier membrane for guided bone regeneration (GBR). However, no study has assessed the influence of the preservation method of HAM for this application. This study aimed to establish the most suitable preservation method of HAM for GBR. Fresh (F), cryopreserved (C) lyophilized (L), and decellularized and lyophilized (DL) HAM were compared. The impact of preservation methods on collagen and glycosaminoglycans (GAG) content … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 74 publications
3
34
0
Order By: Relevance
“…Gurinsky (2009) reported the ability of processed dehydrated amnion to self-adhere, reducing surgical time and eliminating the need for sutures in the management of gingival recession. Originally designed for ophthalmological use, their current indications have also been extended to wound healing, including diabetic foot, venous leg ulcers and lower third nasal reconstruction (Fetterolf and Snyder, 2012;Koob et al, 2016;Laurent I. et al, 2017;Lullove, 2017;Xue et al, 2018) (Fenelon et al, 2019;Fenelon et al, 2020). We reported in in vivo studies that F-hAM and D-hAM were significantly stronger than C-hAM and L-hAM.…”
Section: Graft Storage and Effect On Its Propertiesmentioning
confidence: 91%
“…Gurinsky (2009) reported the ability of processed dehydrated amnion to self-adhere, reducing surgical time and eliminating the need for sutures in the management of gingival recession. Originally designed for ophthalmological use, their current indications have also been extended to wound healing, including diabetic foot, venous leg ulcers and lower third nasal reconstruction (Fetterolf and Snyder, 2012;Koob et al, 2016;Laurent I. et al, 2017;Lullove, 2017;Xue et al, 2018) (Fenelon et al, 2019;Fenelon et al, 2020). We reported in in vivo studies that F-hAM and D-hAM were significantly stronger than C-hAM and L-hAM.…”
Section: Graft Storage and Effect On Its Propertiesmentioning
confidence: 91%
“…Results suggested that the use of cryopreserved AM with the mesenchymal side in contact with the calvarial defect was the best condition to favor bone regeneration in mice (Fénelon et al, 2018b ). The other study compared four commonly used preservation methods of AM (i.e., fresh, cryopreserved, lyophilized or decellularized, and lyophilized) for GBR procedures in mice tibial defect (Fenelon et al, 2020 ). Covering the defect with lyophilized or decellularized and lyophilized AM significantly enhanced early bone formation.…”
Section: Resultsmentioning
confidence: 99%
“…The wide heterogeneity of animal models (species, localization and size of the defect) increases the difficulty of comparing these conditioning methods. One study compared four commonly used preservation methods of AM (i.e., fresh, cryopreserved, lyophilized, and decellularized-lyophilized AM) using the same animal diaphyseal bone defect model in mice (Fenelon et al, 2020 ). No significant difference was observed between the empty defect and the defect covered either by fresh or cryopreserved AM, whereas lyophilized and decellularized-lyophilized AM significantly enhanced early bone regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…The hAM controls the scarring formation through the reduction of fibrosis [34]. This effect is achieved by the downregulation of TGF-b and its receptor expression [35]. The hAM has been used in different surgical subspecialties; it can be used as a dressing or as a transplanted graft.…”
Section: Human Amniotic Membrane In Other Surgical Specialitiesmentioning
confidence: 99%